2019
DOI: 10.1080/15384047.2019.1617562
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic-substrate-1 associated protein X-1 (HAX-1) regulates liver cancer cells growth, metastasis, and angiogenesis through Akt

Abstract: The aim of this study was to investigate the effects and mechanisms of hematopoietic-substrate-1-associated protein X-1 (HAX-1) on liver cancer cells. Information on HAX-1 from liver cancer patients was analyzed by the Cancer Genome Atlas (TCGA) program. Cell migration and invasion abilities were respectively tested by scratch assay and transwell assay. Tube formation assay was applied to detect angiogenesis protein and mRNA was determined using quantitative real-time polymerase chain reaction (qRT-PCR) and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
4
8
0
Order By: Relevance
“…Tumor metastasis will result in less desired treatment outcomes of patients with liver cancer (37). The present data suggested that upregulated HAX1 expression promoted the growth, migration and invasion of liver cancer cells, whereas HAX1 knockdown produced the opposite effects, which were in accordance with the results of previous studies (17,34). The present data further confirmed that HAX1 is a tumor oncogene of liver cancer development and might be an underlying target for the treatment of liver cancer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Tumor metastasis will result in less desired treatment outcomes of patients with liver cancer (37). The present data suggested that upregulated HAX1 expression promoted the growth, migration and invasion of liver cancer cells, whereas HAX1 knockdown produced the opposite effects, which were in accordance with the results of previous studies (17,34). The present data further confirmed that HAX1 is a tumor oncogene of liver cancer development and might be an underlying target for the treatment of liver cancer.…”
Section: Discussionsupporting
confidence: 93%
“…HAX1 is a prognostic factor and is abnormally expressed in several types of cancer ( 31 - 33 ). Similar to previous results ( 34 ), the present data suggested that high HAX1 expression was associated with poorer prognosis in the liver cancer tissues and cell lines examined. The data demonstrated that HAX1 might be an oncogene for liver cancer progression and have diagnostic and prognostic values for liver cancer.…”
Section: Discussionsupporting
confidence: 92%
“…7B). These results were consistent with those of certain previous studies suggesting that PIK3CA overexpression promotes angiogenesis (19)(20)(21)(22).…”
Section: Overexpression Of Pik3ca Promotes Sunitinib Resistance In Rccsupporting
confidence: 93%
“…PIK3CA was involved in the PI3K/AKT pathway, which plays a crucial biological role in cell growth, proliferation, apoptosis, angiogenesis, autophagy and other cell processes. The disruption of this pathway leads to a range of diseases, including cancer (19)(20)(21). The present study verified the results of ChIP with co-IP, and PIK3CA was proven capable of combining with QPCT (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation